Promoting active transportation: A comparative assessment of paths and prices - Darja Mihailova; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
The time people spend traveling has far reaching implications for their health and for environmental outcomes. Urban planning paradigms - such as that of the '15-minute city' - have consequently endeavoured to bring key services and amenities to residents within a walkable or cycleable 15-20-minute distance. These efforts notwithstanding, the policy levers that influence travel-related time allocation remain poorly understood. Drawing on a panel of household travel data from Germany covering 2005 to 2020, the present study analyses the role of two such levers - bicycle/pedestrian paths and fuel prices - as determinants of time allocation across modes. We start with a descriptive analysis that identifies a stable average travel time expenditure ranging between 65 - 70 minutes for women and 75 - 80 minutes for men until 2020, when it dropped precipitously as COVID-19 spread. We subsequently estimate fractional response models to identify the influence of the policy variables on time expenditures across motorized, nonmotorized, and public transit modes. We complete the analysis by feeding the model estimates into the World Heath Organization's on-line Health and Economic Assessment Tool (HEAT) to quantify the health and environmental impacts of the planned expansion of the bike path network in the city of Munich, comparing this with the impact of Germany's recently introduced carbon tax on fuel. Both measures yield substantial benefits, with the implementation of the tax yielding a considerably higher benefit/cost ratio owing to its lower cost of implementation. – – Die Zeit, die die Menschen unterwegs verbringen, hat weitreichende Auswirkungen auf ihre Gesundheit und auf die Umwelt. Stadtplanungsparadigmen - wie das der "15-Minuten-Stadt" - haben folglich versucht, den Bewohnern wichtige Dienstleistungen und Annehmlichkeiten in einem Umkreis von 15-20 Minuten zu Fuß oder mit dem Fahrrad zugänglich zu machen. Trotz dieser Bemühungen sind die politischen Hebel, die die reisebezogene Zeiteinteilung beeinflussen, nach wie vor nur unzureichend bekannt. Die vorliegende Studie stützt sich auf ein Panel von Mobilitätsdaten aus Deutschland für den Zeitraum von 2005 bis 2020 und analysiert die Rolle von zwei solchen Hebeln - Fahrrad-/ Fußgängerwege und Kraftstoffpreise - als Determinanten der verkehrsmittelübergreifenden Zeiteinteilung. Wir beginnen mit einer deskriptiven Analyse, die einen stabilen durchschnittlichen Reisezeitaufwand zwischen 65 und 70 Minuten für Frauen und 75 und 80 Minuten für Männer bis zum Jahr 2020 ermittelt, der dann mit der Ausbreitung von COVID-19 sprunghaft abnimmt. Anschließend schätzen wir ökonometrische Modelle, um den Einfluss der politischen Variablen auf den Zeitaufwand für motorisierte, nichtmotorisierte und öffentliche Verkehrsmittel zu ermitteln. Wir schließen die Analyse ab, indem wir die Modellschätzungen in das Online Health and Economic Assessment Tool (HEAT) der Weltgesundheitsorganisation einspeisen, um die Auswirkungen des geplanten Ausbaus des Radwegenetzes in der Stadt München auf die Gesundheit und die Umwelt zu quantifizieren und dies mit den Auswirkungen der kürzlich in Deutschland eingeführten Kohlenstoffsteuer auf Kraftstoffe zu vergleichen. Beide Maßnahmen bringen erhebliche Vorteile mit sich, wobei die Einführung der Steuer aufgrund der geringeren Umsetzungskosten ein deutlich höheres Nutzen-Kosten-Verhältnis aufweist.
Keywords: D61; R23; R48; 330; Mode choice; time allocation; bicycle/pedestrian paths; fuel prices; Health Economic Assessment Tool